1984
DOI: 10.1073/pnas.81.8.2525
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome 20 deletion in human multiple endocrine neoplasia types 2A and 2B: a double-blind study.

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

1985
1985
1997
1997

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 33 publications
3
9
0
Order By: Relevance
“…For example, it has been shown that medullary carcinoma of the thyroid arises from a single clone of parafollicular cells [Baylin et al, 1978]. More recently, MEN II (which comprises medullary carcinoma of the thyroid) has been associated with dele tions on the short arm of chromosome 20 [Babu et al, 1982], and chromosome dele tions have been found to be associated with the activation of oncogenes in several tumor models [Klein, 1981]. It remains to be seen whether a similar mechanism is in volved in MEN syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been shown that medullary carcinoma of the thyroid arises from a single clone of parafollicular cells [Baylin et al, 1978]. More recently, MEN II (which comprises medullary carcinoma of the thyroid) has been associated with dele tions on the short arm of chromosome 20 [Babu et al, 1982], and chromosome dele tions have been found to be associated with the activation of oncogenes in several tumor models [Klein, 1981]. It remains to be seen whether a similar mechanism is in volved in MEN syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Twelve of 13 MEN-II patients and one of seven controls were scored as having the 20p12.2 deletion (Fig. 1, χ 2 = 12.58, P<0.001) previously reported by Babu et al [7] and Butler et al [8].…”
Section: High-resolution Chromosomesmentioning
confidence: 96%
“…Prometaphase and late prophase spreads were located and two or three cytogeneticists independently scored each chromosome 20 pair for the 20p deletion. All scoring was done through the microscope to maximize optical resolution, similar to the procedure described by Babu et al [7] and Butler et al [8]. Nine to 24 cells without overlap or twist of the short arm of chromosome 20 at the 700-1200 band level were identified and analyzed.…”
Section: High-resolution Chromosomesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data for possible assignment for MEN2A to chromosome 20 because of an interstitial deletion at pl2.2 (Van Dyke et al 1982) were fully reported (Babu et al, 1984).…”
mentioning
confidence: 99%